2023
DOI: 10.1146/annurev-cellbio-011723-021442
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Regeneration and Fibrosis in the Endometrium

Claire J. Ang,
Taylor D. Skokan,
Kara L. McKinley

Abstract: The uterine lining (endometrium) regenerates repeatedly over the life span as part of its normal physiology. Substantial portions of the endometrium are shed during childbirth (parturition) and, in some species, menstruation, but the tissue is rapidly rebuilt without scarring, rendering it a powerful model of regeneration in mammals. Nonetheless, following some assaults, including medical procedures and infections, the endometrium fails to regenerate and instead forms scars that may interfere with normal endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 192 publications
(250 reference statements)
0
4
0
Order By: Relevance
“…A large number of MSCs can be obtained from the umbilical cord, which is safe and convenient, and overcomes the shortcomings of bone marrow MSCs whose number and proliferative and differentiation potentials decline with age, and which have a high rate of viral infections, allowing for a wide range of clinical applications [ 22 , 23 ]. Scarred uterus as one of the most common adverse effects after cesarean section, collagen fibrin deposition is one of the main problems, which affects cell proliferation, differentiation, and migration, which is mainly due to fibroblast proliferation and overproduction of ECM [ 24 ]. Most of the current treatments are aimed at the prevention of uterine adhesions and intra-abdominal adhesions in the relevant organs [ 25 ], and most studies on the molecular signaling and cellular mechanisms of fibrosis in various organs have focused on the liver, kidney, lung, heart, or skin [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of MSCs can be obtained from the umbilical cord, which is safe and convenient, and overcomes the shortcomings of bone marrow MSCs whose number and proliferative and differentiation potentials decline with age, and which have a high rate of viral infections, allowing for a wide range of clinical applications [ 22 , 23 ]. Scarred uterus as one of the most common adverse effects after cesarean section, collagen fibrin deposition is one of the main problems, which affects cell proliferation, differentiation, and migration, which is mainly due to fibroblast proliferation and overproduction of ECM [ 24 ]. Most of the current treatments are aimed at the prevention of uterine adhesions and intra-abdominal adhesions in the relevant organs [ 25 ], and most studies on the molecular signaling and cellular mechanisms of fibrosis in various organs have focused on the liver, kidney, lung, heart, or skin [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that macrophages collect in the peritoneal cavity of people with endometriosis, but whether they can clear displaced endometrial fragments is still unclear [100] . EVs produced from human endometrial stromal cells were observed to promote the formation of endometriotic lesions in mice [101] . Research suggests that elevated levels of circulating total cell-derived EVs in patients with deep-infiltrating endometriosis may cause immune system dysfunction, thereby promoting endometriosis development.…”
Section: Extracellular Vesicle and Endometriosismentioning
confidence: 99%
“…The menstrual cycle is divided into three stages: proliferative, secretive, and menstrual period [ 16 ]. The successful transition between the menstrual and proliferative periods is a key factor determining endometrial regeneration, during which HIF-1α plays a crucial role as a regulatory factor for repairing damaged spiral arterioles and achieving endometrial re-epithelialization [ 17 , 18 ].…”
Section: Physiological Roles Of Endometrial Hif-1αmentioning
confidence: 99%